The genus Ceratophyus Fischer von Waldheim, 1824 (Coleoptera: Geotrupidae) in China, along with description of a new species - Král, David; Jákl, Stanislav; Lu, Yuanyuan; Bai, Ming (Zootaxa, 2020)
Ceratophyus amdoensis Král & Jákl, new species from Gansu and Qinghai Provinces of China is described, illustrated and compared with its congeners so far known from China and adjacent countries. A key to identification of males of Chinese species of Ceratophyus Fischer von Waldheim, 1824 is provided. Ceratophyus polyceros (Pallas, 1771) is excluded from the fauna of China. First province records of C. dauricus (Jekel, 1866) from Hebei (China) and Hentiy (Mongolia) and first province records of C. sinicus Zunino, 1973 from Hebei, Ningxia and Shaanxi (China) are reported. Distribution of five species so far known from China is summarized and mapped.